Competitive removal mechanism to simultaneously incarcerate bisphenol A, triclosan and 4-tert-octylphenol within beta-cyclodextrin crosslinked citric acid used for encapsulation in polypropylene membrane protected-micro-solid-phase extraction. (December 2022) - Hafiz Rozaini, Muhammad Nur'; Saad, Bahruddin; Lim, Jun Wei; Yahaya, Noorfatimah; Ramachandran, Muggundha Raoov; Mohd Ridzuan, Nur Diyan; Kiatkittipong, Worapon; Pasupuleti, Visweswara Rao; Lam, Sze Mun; Sin, Jin Chung
Abstract: Endocrine disrupting compounds (EDCs) are extensively found in the environment and severely impacting human health. In addressing this issue, the beta-cyclodextrin crosslinked citric acid (BCD-CA) had been previously employed in membrane-protected micro-solid phase extraction for sequestering EDCs from water medium; and the findings revealed that BCD-CA possessed a selectivity property. On that account, the potential of BCD-CA towards competitive adsorption of selected EDCs was investigated in terms of adsorption mechanism and selectivity property. Factors that affected the removal efficiencies such as sample pH, sorbent dosage, contact time and initial concentration were evaluated. The characterization results revealed that the carbon percentage of BCD-CA had increased by 2.04%, while the hydrogen percentage had reduced by 1.83%, signifying the successful crosslinking of BCD-CA. Besides, the amount of active BCD was calculated to be 3.2 × 10 −7 mol, while the amount of carboxyl group was 2.48 × 10 −5 mol per 4 mg of BCD-CA. Moreover, BCD-CA was stable in an aqueous medium with the zeta potential obtained at −36.5 mV and had a high-water retention capacity (∼150%). The competitive adsorption mechanism by BCD-CA with EDCs followed the pseudo-second-order kinetics and Freundlich isotherm, suggesting that the adsorption process was dominated by chemisorption on the heterogeneous surface of the adsorbent. Thermodynamic results revealed that adsorption of 4- tert -octylphenol had the most negative ΔG value, indicating most favorable to be adsorbed by BCD-CA as opposed to triclosan and bisphenol A, which was coherent with the apparent formation constant results. These unique properties manifested the practicality of BCD-CA as a selective adsorbent to detect and remove EDCs from the water medium. Graphical abstract: Image 1 Highlights: Beta-cyclodextrin crosslinked citric acid was applied for competitive removal. Three endocrine disruptor compounds (EDCs) were removed simultaneously. Beta-cyclodextrin crosslinked citric acid was selective towards 4- tert -octylphenol. Kinetics and thermodynamics determined the mechanism of competitive adsorption.